Excellent Completion Rate of 8-Weeks Hepatitis C Treatment in Prison; Results of French National Study. - Jean-Marie, RUIZ; Philippe, ALARCON; Chloé, GOBIN; Jean-Claude, GUICHARD; Aurore, BARON (Journal of Advanced Pharmaceutical Science And Technology, 2019)
Rationale Prisons are major reservoirs of hepatitis C virus (HCV) in which a therapeutic approach has been particularly difficult so far. Prevalence of viral hepatitis C (HCV) is higher in prison environment in France than in the general population and is estimated to be 4,8%. The impact in prison environment is little-known as based on local studies.  Inmate health care falls under USMP (prison setting medical unit), hospital specific units as by the january 18, 1994 law. Access to antiviral c treatment for inmates has always been difficult in France, would it be for interferon and ribavirin or use of protease inhibitors, with less than 20% of treated patients. French recommendations for HCV screening recommend systematic screening of inmates. The arrival of all oral therapies by direct antiviral agents (DAA) with shorter treatment times was an opportunity for doctors to propose a treatment and the patient to accept it. In 2014, the French guidelines recommended that HCV carriers in prison should systematically be treated independently of the stage of fibrosis. Objective of the Study PH8 Our objective was to evaluate the completion rate of an 8-week antiviral C treatment by sofosbuvir / ledipasvir regimen in non-cirrhotic genotype 1 patients in deprivation of liberty and achieve sustained virological response (SVR) and to measure the effectiveness of an 8-week treatment (by protocol analysis). Methodology prospective non-interventional multicenter trial among inmates with chronic hepatitis C genotype 1 with METAVIR fibrosis score F0 to F2 and who will receive a daily combination of sofosbuvir / ledipasvir for 8 weeks. Results 6 prison medical units included 115 consenting patients: there were 81% men, mean age 41 years (21 to 64 years). Route contamination was drug injection for 85%. HCV genotype was 1a for 74%, 1b for 24% and 2% none differenciated 1. Fibroscan mesure was available in 89 patients (mean score 3,5 KPa). Fibrotest was available in 37 patients with mean value 0.21. Eleven patients had Fibroscan and Fibrotest; 69% of patients were F0, 22% F1 and 9% F2. Average time between diagnosis and start of treatment was 3 weeks. We are sure that 109 patients (95%) completed DAA 8 weeks treatment; only 2 stopped DAA treatment before 8 weeks and 4 had no follow up after end of detention. HCV viral load was measured at W2 for 90 patients (78%), at W4 for 92 patients (78%), at end of treatment for 92 patients (78%), one month after treatment for 90 patients (78%) and 3 months after for 95 patients (93%). Only one viral load was positive, one month after treatment. Patient was retreated by sofosbuvir / velpastasvir. All HCV viral load 3 months after treatment negative; one patient took DAA only 6 weeks was cured. Conclusions In these study PH8, we observed completion rate of 94% for included patients in patient with 8 weeks ledipasvir/sofosbuvir regimen; data missed for only 4 patients and one relapsed. Short DAA treatment was efficient in prisoners and could be preferred in specific population.
Keywords: hepatitis C; direct antiviral agents; treatment